A study on the factors that affecting the effectiveness in training at Syarikat Air Negeri Sembilan Sdn Bhd / Fatin Nadia Aziz Jaffar - Aziz Jaffar, Fatin Nadia (Faculty of Business and Management, 2019)
Introduction:Training in organizations is a strategic human resources function. Therefore, organization need to ensure that training in the organization is effective. The main objective of the research is to determine the most influence factors that affect the training in SAINS. The factors are trainer characteristic, training content and training environment. This study is aimed to test the relationship between trainer characteristic, training content and training environment with the effectiveness in training at Syarikat Air Negeri Sembilan Sdn Bhd. Researcher used questionnaires as a main instrumental in data collection method. The researcher was distributed 103 questionnaires to the respondents at SAINS. After data had been collected, data was analysed using SPSS version 22. Result: The result indicated that there is a positive relationship between trainer characteristic, training content and training environment in SAINS. Conclusion: Overall, it can be concluded that the most factor that affect the effectiveness training in SAINS are training environment, training content and follow by trainer characteristic .The discussion of study implications and future research will be explained at the end of this study.